KEPENTINGAN TIONGKOK TERHADAP KONFLIK KACHIN DI MYANMAR TAHUN 2011-2013 - Muhammad Rizky Reza Lubis; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research examines the dynamics of internal conflict on Myanmar, especially in Kachin State which has affected Tiongkok Policy toward Myanmar. Since President U Thein Sein’s government ascended to the power in March 2011, Myanmar’s political spring is gradually moving ahead. However, admit the brighter progress, there are struggles and frustrations embedded. Armed conflict between Kachin Independent Organizations (KIO) and government’s troops (Tatmadaw) is still going on. The Kachin conflict has been a policy challenge for Tiongkok. Border tranquility, the protection of Chinese investments and the prevention of expanding US influence are the top three considerations for all border regions. The Kachin conflict has disrupted Tiongkok’s border security and jeopardized its economic investments in the region.The writer collects data from books, encyclopedia, journal, mass media and websites to analyze the Tiongkok’s interest on Kachin Conflict. This research applied neo-realis paradigm and intervention concept from J.G. Strake. The theories applied in this research are objectivity theory from Paul R. Viotti and Mark V. Kauppi on International and World Politics – Security, Economy, IdentityThis research shows that how the Kachin conflict affects these interests of Tiongkok has played a determining role in Tiongkok’s policy toward the conflict. Tiongkok’s most significant policy adjustment on the Kachin conflict was intervention in the negotiations. Tiongkok offered to resolve this difference by providing place for the talks. In addition, Tiongkok also explicitly guaranteed the security of all participants, sending armed police to guard the perimeter. To strengthen policy coordination and implementation, Tiongkok for the first time created a ―Special Envoy on Asian affairs‖ to ―participate in related Sino-Myanmar affairs‖Keywords: Myanmar, Tiongkok, Kachin Conflict, Intervention